PERAN AKTIF PEKERJA SOSIAL DALAM PENANGANAN ORANG DENGAN GANGGUAN JIWA DI PANTI SOSIAL BINA LARAS HARAPAN SENTOSA 3 CIRACAS - JAKARTA TIMUR - Mayaut, Flores George; Asrori, M. (Jurnal Insani, 2020)
This analytical descriptive study discusses the role of social workers in social services for People with Mental Disorders (Orang Dengan Gangguan Jiwa/ODGJ) at the Bina Laras Harapan Sentosa 3 Panti Sosial, Ciracas, East Jakarta. Problems with ODGJ include clients who rarely worship, are less interested in participating in skill activities, appear often daydreaming, aloof, anxious and sad, are less productive in participating in skill activities, and have difficulty in reading, writing and arithmetic. The role of social workers in providing services to ODGJ includes (1) as a counselor (2) as an educator/educator (3) as a motivator (4) as a problem solver/problem solver (5) as a broker (6) as a therapist and (7) as a facilitator. The results of the implementation of the role of social workers show that: (1) the client has been seen starting to pray and participate in routine recitation activities (2) the client has started to often participate in activities in the orphanage (3) the client is more cheerful and rarely daydreams anymore because diverted to more positive activities (4) the client has begun to concentrate more on following salon skills and is trying to pursue it so that he can see skills in doing special hair care (5) the client seems to have started to be able to read, write and count well. Researchers suggest Panti Sosial Bina Laras Harapan Sentosa 3, in order to be able to provide skills for People with Mental Disorders so that they have more choices for skills that are followed and increase the profession of social workers in the field of handling mental disorders.